FORECASTING AN EMERGENT SYSTEMIC TREND IN NEUROPHARMACOLOGY - MARGINEANU, Doru Georg (Studia Universitatis Babeș-Bolyai Chemia, 2021)
Neuropharmacology (NP), which evolved along with scientific medicine, got treatments for several common disorders of the nervous system. But, most of the NP drugs are just symptomatic, reducing only the manifestations of brain pathologies. Also, for main neuro-psychiatric pathologies (e.g. the neurodegenerative diseases) there is very poor or no medication, and the output of NP drug discovery declined in the last decades. This review paper argues that those drawbacks derive from the reductionist NP leaning towards single–target selective drugs, at odds with the essential complexity of brain functioning and the multifactorial causality of its pathologies. Most active neuro-drugs (e.g. valproate and levetiracetam) are in fact multi-mechanistic since they have been selected by phenotypic screening in vivo, not by single-target binding in vitro. A putative solution of the relative NP stagnation seems to come with the emergent systemic approach of network pharmacology. A plausible flowchart of the main stages of a network NP drug discovery endeavor is finally sketched.